Prevalence and Risk Factors of Reduced Bone Mineral Density in Systemic Lupus Erythematosus Patients: A Meta-Analysis. (20th February 2019) - Xia, Jumei; Luo, Ran; Guo, Shuiming; Yang, Yi; Ge, Shuwang; Xu, Gang; Zeng, Rui
Abstract : Background . We aimed to conduct a meta-analysis concerning the frequency and risk factors of reduced bone mineral density (BMD) in systemic lupus erythematosus (SLE) with evidence from published studies. Methods. A comprehensive literature search was conducted based on the EMBASE, Web of Science, PubMed, and Cochrane Library databases up to March 5th, 2017. Eligible studies reported any prevalence of reduced BMD in SLE patients. All risk factors with odds ratios or risk ratios associated with reduced BMD were extracted. Results . 71 reports with 33527 SLE patients were included. Low BMD, osteopenia, and osteoporosis at any site were presented, respectively, in 45%, 38%, and 13% of the SLE patients. The prevalence of osteoporosis increased with the advancing of age, while U-shaped associations between age and the prevalence of low BMD and osteopenia were found. Lumbar spine was indicated to have higher prevalence of osteoporosis. Age, disease duration, drugs use, and many other factors were identified as predictors of reduced BMD. Conclusion . Low BMD, osteoporosis, and osteopenia appeared to be prevalent in patients with SLE. Risk factors of reduced BMD were various.